2015
DOI: 10.1002/bit.25616
|View full text |Cite
|
Sign up to set email alerts
|

Interlinked population balance and cybernetic models for the simultaneous saccharification and fermentation of natural polymers

Abstract: Simultaneous Saccharification and Fermentation (SSF) is a process where microbes have to first excrete extracellular enzymes to break polymeric substrates such as starch or cellulose into edible nutrients, followed by in situ conversion of those nutrients into more valuable metabolites via fermentation. As such, SSF is very attractive as a one-pot synthesis method of biological products. However, due to the co-existence of multiple biochemical steps, modeling SSF faces two major challenges. The first is to cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…This is expected, as detailed metabolic routes were not included in the model. Structured modelling approaches such as cybernetic modelling (Ho et al, 2015;Ramkrishna and Song, 2012), genome-scale models (GEMs) or structured kinetic models (Heijnen, 2005;Kerkhoven et al, 2015) may enable more rigorous description of the observed phenomena. However, the goal here is to describe a model with low computational load to be applied in bioreactor simulations.…”
Section: Growth Model For Pichia Pastorismentioning
confidence: 99%
“…This is expected, as detailed metabolic routes were not included in the model. Structured modelling approaches such as cybernetic modelling (Ho et al, 2015;Ramkrishna and Song, 2012), genome-scale models (GEMs) or structured kinetic models (Heijnen, 2005;Kerkhoven et al, 2015) may enable more rigorous description of the observed phenomena. However, the goal here is to describe a model with low computational load to be applied in bioreactor simulations.…”
Section: Growth Model For Pichia Pastorismentioning
confidence: 99%
“…With appropriate initial conditions, the above ODEs can be solved to obtain C i ( t )'s. In general, kij ( j = α or γ) is constant, but there are cases where kij is DP‐dependent or it may assume forms that are related to the nature of the process . For the sake of comparison with the continuous distribution, molar concentration ( C i ) in the discrete equations above can be used interchangeably with molar concentration density ( c i ) as the latter equals C i divided by a unit DP interval.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…$O(10 5 )) can be solved by using commercial ODE integrators for the purpose of validation. [38] In general, Equations (1)-(3) form a linear system of ODEs which can be written in the following form:…”
Section: Chain-end Scissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These unstructured models are often unable to provide a mechanistic understanding of coupled multi‐physics phenomena in cellulose bioconversion, including SSF and CBP. By contrast, Ho et al (2015a, 2015b) made a significant step forward in this regard by accounting for the coupled dynamics of polymeric saccharification and regulation of cellular metabolism during fermentation by interlinking population balances and cybernetic models. Despite improved predictions compared to existing approaches, this model still has limited capability of providing mechanistic details due to: (1) oversimplification of fermentation pathways into a single‐step reaction and (2) lack of consideration of extensive recalcitrance through heterogeneous structure and properties of cellulose.…”
Section: Introductionmentioning
confidence: 99%